Manichaeism and its legacy - Coyle, John Kevin. (Nag Hammadi and Manichaean Studies, 2009)
This volume reproduces nineteen chapters and articles published between 1991 through 2008, on Manichaeism, and its contacts with Augustine of Hippo, its most famous convert and also best-known adversary. The contents are divided into four parts: perceptions of Mani within the Roman Empire, select aspects of Manichaean thought, women in Manichaeism, and Manichaeism and Augustine. Though these chapters and articles reproduce their originals, adjustments have been made to include cross-referencing, newer editions, and the like, all with the aim of rendering them more accessible to a new readership among those who follow the fortunes of Mani's religion in the Roman Empire and/or the "Manichaean" aspects of Augustine of Hippo.